Increasing adolescents' awareness of the impact of promiscuity through educational socialization - Dewi Nurhanifah; Muhammad Sharil (Edukasi Ilmiah Indonesia, 2024)
The influence of promiscuity among adolescents is increasingly a serious concern because of the negative impacts it causes, such as drug abuse, pregnancy out of wedlock, and declining academic achievement. This community service program aims to increase adolescents' awareness of the impact of promiscuity through educational socialization. The methods used include interactive counseling, group discussions, and case simulations. This activity in secondary schools involves students, teachers, and parents. The results of this activity are expected to increase adolescents' knowledge about the dangers of promiscuity, as well as encourage them to develop critical thinking skills in dealing with the negative influences of the social environment. In addition, this program aims to strengthen social support from families and schools in guiding adolescents to live healthy and productive associations. Through this approach, it is hoped that awareness and wiser behavior of adolescents can be formed in daily interactions.